Ecotoxicological tests with ballast waters and marine waste management from ships - Ramírez Caján, Alfonso (2019)
This research focused on the analysis of the ecotoxicological effects of ballast water transported by ships arriving from international trips to the port of Callao on juveniles of Odontesthes regia regia (Pejerrey), through an acute bioassay that determined the mortality of more than 50% of the organisms from the C3 concentration; as well as an evaluation of physicochemical and microbiological parameters that revealed pH values ​​outside the normal range of marine waters with the presence of heterotrophic bacteria in quantities of 210 units. Likewise, the management of the waste that the ships disposed of through naval devices and aquatic reception facilities during the years of 2017 to 2019 in 11 seaports of Peru was evaluated, being the port of Callao the largest receiver with 1,044.95 m3 of mixtures oily and 385.71 t of waste and the port of Chancay the one of lower transfer with 28.99 m3 of oily mixtures and 16.19 t of waste, due to the presence of a greater number of ships in the shipping fleet and to the concentration of aquatic activities in each zone of operation.